Towards structured, block-based PDF - Smith, Philip N.; Brailsford, David F. (John Wiley Ltd, 1995)
The Portable Document Format (PDF), defined by Adobe Systems Inc. as the basis of its Acrobat product range, is discussed in some detail. Particular emphasis is given to its flexible object-oriented structure, which has yet to be fully exploited. It is currently used to represent not logical structure but simply a series of pages and associated resources. A definition of an Encapsulated PDF (EPDF) is presented, in which EPDF blocks carry with them their own resource requirements, together with geometrical and logical information. A block formatter called Juggler is described which can lay out EPDF blocks from various sources onto new pages. Future revisions of PDF supporting uniquely-named EPDF blocks tagged with semantic information would assist in composite-pagemakeup and could even lead to fully revisable PDF.